Applied and computational matrix analysis : MAT-TRIAD, Coimbra, Portugal, September 2015 Selected, revised contributions /: MAT-TRIAD, Coimbra, Portugal, September 2015 Selected, revised contributions. (2017) - Unknown
No abstract available